O percurso do outro: um currículo para a outreidade como educação libertadora a partir de Lévinas, Dussel e Freire - Souza, Francisco Josivan de (2013)
The aim of this thesis is discussing the otherness´s field and, therefore, the living together at school as a communitarian ethos to promote social transformation. Starting from the fundamental statement of the student´s otherness, just like the professor´s, what is expected from this thesis is the theoretical discussion about a curriculum that considers the course of the Other on her daily routine, which demands the curriculum itself to be another in order to put a ground for this purpose, I support myself: on the philosophical contributions of Emmanuel Lévinas and his statement to recognize the Other as someone absolutely incomprehensible and impossible to be considered as just a thing, as well as his critics towards the ontology; on the philosophical constructions of Enrique Dussel and his critics to the modernity as the Eurocentric dissimulator of the Latin-American s otherness, rendered by the solipsistic and conqueror European culture; and on Paulo Freire, who criticizes the oppressive and banking pedagogy and proposes the "education as a practice of freedom" and a pedagogy which, born from the oppressed, produces itself at the same time as produces liberty and critical consciousness. From this point on, this thesis supports the building of a curriculum to the otherness, as an act of liberation, criticizing the reproductive-banking Eurocentric and authoritarian curricular activities, developed by the modern schools and still present at the school´s life. The construction of a curriculum to the otherness is a condition sine qua non to the social transformations and to the Ethics of Liberation